2020
DOI: 10.3389/fped.2020.00225
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Brain-Sparing, Postnatal Cerebral Oxygenation, and Neurodevelopment at 4 Years of Age Following Fetal Growth Restriction

Abstract: Objectives: To assess the role of fetal brain-sparing and postnatal cerebral oxygen saturation (r c SO 2 ) as determinants of long-term neurodevelopmental outcome following fetal growth restriction (FGR).Methods: This was a prospective follow-up study of an FGR cohort of 41 children. Prenatally, the presence of fetal brain-sparing (cerebroplacental ratio < 1) was assessed by Doppler ultrasound. During the first two days after birth, r c SO 2 was measured with near-infrared spectroscopy. At 4 years of age, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Finally, we reviewed the 12 studies that met the inclusion criteria. All of these were longitudinal studies: 11 prospective [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 ] and only one retrospective [ 35 ]. Two of the studies were secondary analyses of randomized clinical trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we reviewed the 12 studies that met the inclusion criteria. All of these were longitudinal studies: 11 prospective [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 ] and only one retrospective [ 35 ]. Two of the studies were secondary analyses of randomized clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…This test analyzes communication, gross and fine motor skills, problem-solving and personal–social interaction. Weschler Intelligence Scale [ 29 , 31 , 35 ]. This test assesses intelligence, verbal comprehension, working memory, processing speed, and the perceptual reasoning index.…”
Section: Resultsmentioning
confidence: 99%
“…Although an angiogenic dysbalance (lower circulating VEGF levels) has also been evidenced in patients with ASD, we have reported in our previous paper that both children also presented with impaired umbilical flow even if no signs of fetal brain-sparing were present. 5,51 Regardless of its origin, VEGFA hypermethylation does not seem to benefit neurodevelopmental outcome.…”
Section: Discussionmentioning
confidence: 97%
“…In a previous study, we found that preferential perfusion of the fetal brain in FGR was associated with better neurodevelopmental outcome at 4 years of age than FGR without fetal brain-sparing. 5 This seemed to be mediated through higher cerebral oxygen saturations as suggested by postnatal tissue oxygenation monitoring with nearinfrared spectroscopy. In the same cohort, we now find a trend toward hypermethylation at the autoregulatory HRE of the HIF1A promoter in the buccal DNA of these children.…”
Section: Discussionmentioning
confidence: 99%
“…This hemodynamic redistribution remains visible after birth as altered cerebrorenal oxygenation, as demonstrated using near-infrared spectroscopy (NIRS) ( 3 , 4 ). Although an increase in cerebral oxygenation is intended as protective, it is debated whether this (fully) benefits neurodevelopmental outcome ( 5 , 6 ). Moreover, redistribution has been associated with impaired cerebral autoregulation ( 7 ).…”
Section: Introductionmentioning
confidence: 99%